Impact of physical layer impairments on multi-degree CDC ROADM-based optical networks - Sequeira, D. G. (2018)
Nowadays, optical network nodes are usually based on reconfigurable optical add/drop multiplexers (ROADMs). Due to exponential growth of internet data traffic, ROADMs have evolved to become more flexible, with multi-degree and their add/drop structures are now more complex with enhanced features, such as colorless, directionless and contentionless (CDC). In this work, the impact of in-band crosstalk, optical filtering and amplified spontaneous emission noise on the performance of an optical network based on multi-degree CDC ROADMs is studied considering 100-Gb/s polarisation division multiplexing quadrature phase-shift keying signals for the fixed grid. We show that, an optical signal can pass through a cascade of 19 CDC ROADMs, based on a route and select architecture with 16-degree, until an optical signal-to-noise ratio (OSNR) penalty of 1 dB due to in-band crosstalk is reached. We also show that the ASE noise addition, due to the increase of the number of CDC ROADMs, is more harmful in terms of OSNR penalty than in-band crosstalk.